Nanotechnology based therapeutic application in cancer diagnosis and therapy - Singh, Ragini (3 Biotech, 2019)
Due to the lack of early diagnosis, cancer remains as one of the leading cause of human mortality. Inability to translate research into clinical trials and also inability of chemotherapeutics delivery to targeted tumor sites are major drawbacks in cancer therapeutics. With the emergence of nanomedicine, several nanoprobes (conjugated with targeting ligands and chemotherapeutic drugs) are developed. It can interact with biological system and thus sense and monitor the biological events with high efficiency and accuracy along with therapy application. Nanoparticles like gold and iron oxide are frequently used in the computed tomography and magnetic resonance imaging applications, respectively. Moreover, enzymatic activity of gold and iron oxide nanoparticles enables the visible colorimetric diagnostic of cancer cells, whereas, fluorescence property of quantum dots and upconversion nanoparticles helps in in vivo imaging application. Other than this, drug conjugation with nanoparticles also reduces the systemic toxic effect of chemotherapeutic drugs. Due to their several unique intrinsic properties, nanoparticles itself can also be employed as therapeutics in cancer treatment by photothermal therapy (PTT) and photodynamic therapy (PDT). Thus, the main focus of this review is to emphasize on current progress in diagnostic and therapeutic application of nanoprobes in cancer.